Blackkklansman [videorecording (DVD)] - Lee, Spike; Washington, John David, 1984-; Driver, Adam; Harrier, Laura, 1990-; Baldwin, Alec, 1958-; Belafonte, Harry, 1927-; Stallworth, Ron (Universal Pictures Home Entertainment, 2018)
Ron Stallworth, an African-American police officer from Colorado, successfully managed to infiltrate the local Ku Klux Klan and became the head of the local chapter.